Pemberdayaan Kader Remaja "SEHATI" Dalam Upaya Mewujudkan Kelurahan Bebas Stunting Di Kelurahan Mantuil - Balqis Maharani; Purnomo Adi Saputra; Olivia Octaviani; Jesika Natalia; Zakiah Husniah; St' Sairah; Nurfatriani Nurfatriani; Oisca Gabe Eidelwis Br. Pardede; Sari Panabela; Putri Hazatun Nufus; Susanti Suhartati (Journal of Community Development, 2025)
The prevalence of stunting in South Kalimantan Province is 40.2% and in 2024 the number of stunted children in Mantuil Village is 72 children, one of the factors causing stunting is the high rate of anemia in adolescents in the Mantuil Village area, in 2023 a total of 115 or 35.7% of adolescent girls experienced anemia. South Banjarmasin Sub-district in 2022 also has the highest percentage of Early Marriage with 130 people dominated by people in the Mantuil Village area with 78 women and 9 men, the high number of Early Marriage cases is the biggest contributor to the incidence of stunting in the Mantuil Village area. The purpose of the activity is the formation of SEHATI Youth Cadres and a sustainable SEHATI Corner to improve public health status and increase adolescent knowledge as a community social action, as a reference in implementing stunting prevention programs in Mantuil Village. The method of implementing this activity which is carried out with the community and with the support of the local government consists of 3 stages, namely: SEHATI Youth Cadre Formation, Cadre Training and Sehati Corner Formation. Forming the Sehati Youth Cadre Institution with a total of 15 teenagers representing each RT in Mantuil Village, then empowering cadres through training activities on stunting, and simple health checks. The result of the implementation of this activity is the establishment of preventive and curative activities related to stunting prevention in Mantuil Village by the Sehati Youth Cadres through counseling activities for all teenagers in Mantuil Village. The evaluation showed a significant increase in the cadres' knowledge and skills. The average pretest score of participants was 45.3%, increasing to 93.3% in the posttest, with an average increase of 48%. Meanwhile, cadres' skills in conducting health education also improved, with an average pretest score of 23.7% and a posttest of 79.7%, showing an increase of 56%. Measurements were made through pretest and posttest tests which included stunting education material and cadre skill practice in conducting health counseling. With the SEHATI Corner, it is hoped that the sustainability of the program can be maintained and continue to provide benefits for adolescents in Mantuil Village in an effort to prevent stunting.